High Security Ubiquitous H-Iot on a Wban-Based Ehr Using Blockchain - Kaschel-Carcamo, H (Institute of Electrical and Electronics Engineers Inc., 2021)
In the last decades the Internet of things IoT has had a great development of health systems. With the incorporation of medicine 4.0, it has allowed the development of software and electronic devices, obtaining various systems applied to Healthcare IoT (H-IoT). Through the use of WBAN (Wireless Body Area Network) the communication systems between sensor nodes allow the measurement of physiological variables which are collected and processed. In order not to compromise the privacy of the data and the security, the use of new technologies that promote safe data, such as the blockchain, is proposed. In this article we present the main concepts and requirements needed to design a high security ubiquitous H-IoT in a WBAN-based EHR using Blockchain. The advantages of implementing a system of this nature in the short or medium term will allow the countries of the world to greatly alleviate the burden on public health institutions, reducing health costs and increasing people s quality of life. © 2021 IEEE.
Keywords: Blockchain; Electronic Health Records (EHR); Interoperability Healthcare Internet of Things (H-IoT); Wireless Body Area Network (WBAN)